KOMUNIKASI DATA LORA UNTUK MENDETEKSI GANGGUAN PADA JARINGAN DISTRIBUSI LISTRIK: untuk KOMUNIKASI DATA LORA UNTUK MENDETEKSI GANGGUAN PADA JARINGAN DISTRIBUSI LISTRIK - Tukan, Carly (Universitas Islam Balitar Blitar, 2025)
Disturbances in power distribution networks, such as growing trees or the presence of animals near electrical cables, can disrupt electricity flow and pose safety risks. To address this, a remote monitoring system was developed using LoRa (Long Range) communication for long-distance, low-power data transmission. The system integrates a JSN-SR04T ultrasonic sensor to measure the distance between objects (e.g., trees) and power lines. When the detected distance is less than the safe limit of 2.5 meters, a warning buzzer is triggered, and the ESP32-CAM module captures an image of the surrounding area. Data and images are transmitted via LoRa RA-02 in a point-to-point setup and displayed in real-time using an IoT platform. Testing results show that the ultrasonic sensor provides accurate measurements with an average error of 1.12%. LoRa communication remained reliable up to approximately 348 meters, with minor interference caused by physical obstacles. The ESP32-CAM successfully captured images when objects were detected. This system proves to be effective for early detection and monitoring of potential disturbances in power distribution networks